SEMANTIC ANALYSIS OF STYLISTIC DEVICES (METAPHOR, METONYMY AND IRONY) IN THE STORY “THE LITTLE PRINCE” BY ANTOINE DE SAINT-EXUPÉRY (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article identifies the semantic analysis of stylistic devices in children’s storybook, named “The Little Prince”. The author of this children’s book, who is French and not an English native, makes it appealing. This paper aims to explore the stylistic devices (metaphor, metonymy and irony) used in the storybook and analyse them. The given examples are collected from the storybook by reading thoroughly. Then the sentences are analysed in the results part of the article.